The Historical and Legal Development of Pre-Trial Investigation Procedures in The Criminal Process of Uzbekistan - Khidoyatov Bakhtiyar Batirovich (International Journal of Law And Criminology, 2025)
This article presents a comprehensive, chronological analysis of the evolution of pre-trial proceedings within the criminal process of Uzbekistan. It systematically examines the historical origins and development of pre-investigation procedures, inquiries, and preliminary investigations. The study critically evaluates the effectiveness of different forms of pre-trial criminal procedures across various historical periods. Furthermore, it substantiates the necessity for the introduction of novel legal mechanisms aimed at enhancing the regulation and efficiency of pre-investigation checks, inquiries, and preliminary investigations, thereby contributing to the optimization of the criminal justice process.